Seedtime on the Cumberland - Arnow, Harriette Louisa Simpson, 1908-1986 (JSTOR EBA., 2013)
The author's roots ran deep into the Cumberland River country of Kentucky and Tennessee, and out of her closeness to that land and its people comes this remarkable history. The first of two companion volumes, this book captures the triumphs and tragedies of everyday life on the frontier, a place where the land both promised and demanded much. In the years between 1780 and 1803, this part of the country presented tremendous opportunity to those who endeavored to make a new life there. Drawing on an extensive body of primary sources - including family journals, court records, and personal inventories - the author paints a portrait of these intrepid people. Like the midden at some ancient archaeological site, these accumulated items become a treasure awaiting the insight and organization of an interpreter. The book also draws on a medium the author believed in unerringly - oral history, the rich tradition that shaped so much of her own family and regional experience. A classic study of the Old Southwest, this book documents with stirring perceptiveness the opening of the Appalachian frontier, the intersection of settlers and Native Americans, and the harsh conditions of life in the borderlands.